Stakeholder engagement on performance of Police Housing projects in Nairobi County, Kenya - Mary, Elizabeth Vivi (IJRDO - Journal of Business Management, 2021)
The identification of factors necessary for successful implementation of projects is of great importance to many institutions and organizations. In Kenya like other countries, construction industry is one major industry contributing significantly to the socio-economic development and growth. Achieving project implementation on time, within budget, at specified quality standards, and most importantly without unprecedented cost escalations is major criterion of success of project. Generally, a project is considered successful if the project is completed within a stated cost or budget and time. Although the Government of Kenya sets aside huge sums of money to be spent in construction sector, the industry is facing a lot of challenges such as the expenditure exceeding the budget, delay to complete the project in time, the building defects and over-reliance on foreign workers The overall goal of this study was to examine the influence of stakeholder participation on performance of Police Housing Projects in Kenya. The study adopted Resource-dependence theory and Normalization Process Theory. The study adopted a descriptive design. The design facilitated the collection of information on the influence of stakeholder participation on performance of police housing projects in Kenya. The target population was made up of 230 respondents. The study used a sample size of 146 respondents. The questionnaire had both open ended and closed questions. Secondary data was also obtained from the financial statements of the targeted institutions. This assisted in measuring the performance. The data was further coded and entered for analysis using SPSS.  Pearson correlation analysis was used to relate the various study variables.  The results of the study are presented using tables. From the study results, most respondents (69%) indicated that stakeholder engagement highly affects the performance of police housing projects. The study recommends that since stakeholder participation aspects are an important inclination towards performance of police housing projects, the projects should establish an independent stakeholder participation department that identifies, analyses, monitors and controls housing projects. To further improve performance of police housing projects, the stakeholder participation department should educate its stakeholders on the aspects of project management.